Natural history of endometriosis in pregnancy: ultrasound study of morphology of deep endometriosis and ovarian endometrioma - Bean, E.; Knez, J.; Setty, T.; Tetteh, A.; Casagrandi, D.; Naftalin, J.; Jurkovic, D. (Ultrasound in obstetrics & gynecology, 2023)
ABSTRACT Objective To assess the morphological appearance of deep endometriosis and ovarian endometrioma in pregnancy using pelvic ultrasound examination. Methods This was a prospective observational cohort study conducted over 3 years at University College London Hospital, which is a tertiary level referral unit for early pregnancy complications and an accredited endometriosis center. All women who participated provided written consent and were invited for surveillance ultrasound examination at the time of their routine scans in pregnancy. All scans were performed by a single operator to eliminate interobserver variability. The change in size of ovarian endometrioma and nodules was reported as change in their mean diameter. Ovarian endometrioma with irregular thick inner walls, hyperechoic papillary projections and/or high vascularity and hyperechoic nodules with moderate to high vascularity were reported as decidualized. Results Sixty‐five women with a live, normally sited pregnancy and concomitant ultrasound features of deep and/or ovarian endometriosis were included in the study. The median age of the study population was 34 (range, 23–44) years, and the median gestational age at presentation was 7 + 6 (range, 3 + 6 to 18 + 0) weeks. From the cohort, 47/65 (72%) were nulliparous, 48/65 (74%) had a previous diagnosis of endometriosis and 19/65 (29%) conceived via in‐vitro fertilization. There were 10/65 (15% (95% CI, 7–24%)) women with ovarian endometrioma alone, 28/65 (43% (95% CI, 31–55%)) with endometriotic nodules alone and the remaining 27/65 (42% (95% CI, 30–54%)) had both. Of the women with ovarian endometrioma who underwent follow‐up, 29/34 (85% (95% CI, 73–97%)) experienced cyst regression, 2/34 (6% (95% CI, 0–14%)) experienced cyst growth, and in 3/34 (9% (95% CI, 0.0–18%)) women, cyst size was unchanged. In 10/34 (29% (95% CI, 14–45%)), there was complete resolution of all cysts. Of the women with nodules who underwent follow‐up, 43/51 (84% (95% CI, 74–94%)) experienced nodule regression, 2/51 (4% (95% CI, 0–9%)) experienced nodule growth and, in 6/51 (12% (95% CI, 3–21%)) women, nodule size was unchanged. In 4/51 (8% (95% CI, 0–15%)) women, there was complete resolution of all nodules. In 5/37 (14% (95% CI, 3–25%)) women who attended postnatal follow‐up, complete resolution of all endometriotic lesions occurred during pregnancy. In 10/34 (29% (95% CI, 14–45%)) women with ovarian endometrioma and 27/51 (53% (95% CI, 39–67%)) women with nodules, a pattern of growth was observed in the first and second trimesters, followed by regression later in pregnancy. Features of decidualization were observed in 17/34 (50% (95% CI, 33–67%)) women with ovarian endometrioma, most commonly in the first trimester, and in 25/51 (49% (95% CI, 35–63%)) women with nodules, most commonly in the second trimester. Conclusions For the majority of women, despite features of decidualization being common in the first and second trimesters, ovarian endometrioma and deep nodules regress during pregnancy. Morphological changes of endometriosis in pregnancy are difficult to differentiate from characteristics of malignant lesions. Better understanding of the appearance of endometriosis in pregnancy is vital to minimize intervention and help counsel women regarding their condition. © 2023 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.